PENGARUH BRAND HERITAGE YANG DIMEDIASI OLEH BRAND LOYALTY PENGGUNAAN PONSEL CERDAS IPHONE - Febry Nurjanah; Muhartini Salim (Management Insight: Jurnal Ilmiah Manajemen, 2021)
The purpose of this study was to find and analyze the influence of brand heritage mediated by brand image on brand loyalty in the use of iPhone smartphones in Bengkulu city. This research is a quantitative research. The population used in this study were all respondents in the city of Bengkulu who used an iPhone smartphone, with a sample of 144 respondents. Data collection using non probability sampling and analyzed using SEM PLS (partial least square). Based on the analysis, it was found that; 1) Brand heritage has a significant positive effect on brand image on the use of iPhone smartphones in Bengkulu city; 2) brand heritage has a significant positive effect on brand loyalty in the use of iPhone smartphones in Bengkulu city; 3) brand image has a significant positive effect on brand loyalty in the use of iPhone smartphones in Bengkulu city; 4) brand heritage can be partially mediated by brand image on the use of iPhone smartphones for brand loyalty.